Uso del google drive y tareas académicas en estudiantes de educación inicial de la facultad de ciencias de la educación y humanidades Universidad Nacional de la Amazonía Peruana, Iquitos 2021 - Flores Parente, Milagros (2022)
The main objective of this study has been to determine the relationship between the use of google drive and academic tasks in students of Initial Education of the Faculty of Sciences of Education and Humanities at the National University of the Peruvian Amazon Iquitos 2021. As a methodology, has used the relational type of research, with a field, cross-sectional, and bivariate design. The population consisted of 203 initial education students, the sample was census, that is, the 203 students. It was applied to the survey as a data collection technique and two questionnaires as instruments, which were validated at the appropriate time by the judgment of judges. The main conclusion of the study is that the chi-square test = 107.986, p=0.000 indicates that there is a significant relationship between the use of google drive and academic tasks; In addition, Kendall's Tau-b coefficient = 0.681 shows that this relationship is strong and direct and confirms that the hypothesis proposed for the investigation is true.